2017
DOI: 10.1515/afe-2017-0158
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Bainitic Transformation in Austempered Ductile Iron

Abstract: A mathematical model of austenite -bainite transformation in austempered ductile cast iron has been presented. The model is based on a model developed by Bhadeshia [1,2] for modelling the bainitic transformation in high-silicon steels with inhibited carbide precipitation. A computer program has been developed that calculates the incubation time, the transformation time at a preset temperature, the TTT diagram and carbon content in unreacted austenite as a function of temperature. Additionally, the program has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As research has shown (Nofal, 2013;Kuziak et al, 2010), the wide range of the mechanical properties of ADI can be obtained by appropriately selecting isothermal strength parameters leading to the formation of the final microstructure. As part of the research, to calculate the bainite transformation time in ductile cast iron, the mathematical Bhadeshia model (Equation (1)) was used, which was originally used for high-silicon steels (Chester & Bhadeshia, 1997;Olejarczyk-Wożeńska et al, 2017):…”
Section: State Of the Artmentioning
confidence: 99%
“…As research has shown (Nofal, 2013;Kuziak et al, 2010), the wide range of the mechanical properties of ADI can be obtained by appropriately selecting isothermal strength parameters leading to the formation of the final microstructure. As part of the research, to calculate the bainite transformation time in ductile cast iron, the mathematical Bhadeshia model (Equation (1)) was used, which was originally used for high-silicon steels (Chester & Bhadeshia, 1997;Olejarczyk-Wożeńska et al, 2017):…”
Section: State Of the Artmentioning
confidence: 99%